Assessing Political Commitment to Fighting Corruption - Heilbrunn, John; Keefer, Philip (World Bank, Washington, DC, 2012)
Rarely discussed 15 years ago, the commitment of political leaders to reform--that is, their willingness to implement and sustain reform--is now widely accepted as crucial for aid effectiveness. Nowhere is political commitment more important--and more difficult to sustain--than in implementing reforms to fight corruption. Governments increasingly seek external assistance to meet this challenge. More than any other public sector reform, reducing corruption may threaten poltical coalitions and a government's survival--and threats to political survival weaken the resolve of even the most committed leaders. This Note describes methods that might be used to objectively evaluate a government's political commitment to reducing corruption, whether petty, grand or systemic.